2016
DOI: 10.1038/nature19340
|View full text |Cite
|
Sign up to set email alerts
|

The formation of Charon’s red poles from seasonally cold-trapped volatiles

Abstract: A unique feature of Pluto's large satellite Charon is its dark red northern polar cap. Similar colours on Pluto's surface have been attributed to tholin-like organic macromolecules produced by energetic radiation processing of hydrocarbons. The polar location on Charon implicates the temperature extremes that result from Charon's high obliquity and long seasons in the production of this material. The escape of Pluto's atmosphere provides a potential feedstock for a complex chemistry. Gas from Pluto that is tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 41 publications
(46 reference statements)
4
49
1
Order By: Relevance
“…Mordor is the largest observed dark deposit on Charon, and Gallifrey the second‐largest on the encounter hemisphere. However, they might have different deposition mechanisms, for Grundy, Cruikshank, et al () found that Mordor could form from seasonally cold‐trapped volatiles; given that Gallifrey is equatorial, the same argument could not be made. Further hindering a straightforward interpretation, in LEISA spectra, deposits coincident with Ripley crater—which are just dark and not red—are similar to both Mordor and Gallifrey.…”
Section: Unit Interpretation and Discussion Of Interesting Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Mordor is the largest observed dark deposit on Charon, and Gallifrey the second‐largest on the encounter hemisphere. However, they might have different deposition mechanisms, for Grundy, Cruikshank, et al () found that Mordor could form from seasonally cold‐trapped volatiles; given that Gallifrey is equatorial, the same argument could not be made. Further hindering a straightforward interpretation, in LEISA spectra, deposits coincident with Ripley crater—which are just dark and not red—are similar to both Mordor and Gallifrey.…”
Section: Unit Interpretation and Discussion Of Interesting Featuresmentioning
confidence: 99%
“…Charon, the smaller companion in the binary Pluto‐Charon system, is a 606.0 ± 3.0‐km‐radius body (Nimmo et al, ) that NASA's New Horizons spacecraft revealed to be geologically diverse when it flew by in July 2015. Numerous researchers have summarized some of its diverse landforms (e.g., Grundy, Binzel, et al, ; Moore et al, ; Stern et al, ) including its large, red polar deposit (Grundy, Cruikshank, et al, ); global tectonics system (Beyer et al, ); features of its equatorial plains (Beyer et al, ); crater population (Robbins et al, ); and craters with abrupt terminus ejecta (Robbins, Runyon, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mordor Macula itself appears to have a very different color signature than the rest of Charon ( Grundy et al, 2016b ), but its structural history is difficult to discern. The stereo data show a very distinct topographic ridge that appears to bound the majority of the dark red material of Mordor Macula running from approximately longitude 215° (where the topographic data begin in the west) to longitude 21° where the ridge (and the dark red material) is interrupted by the Dorothy Gale crater.…”
Section: Observationsmentioning
confidence: 99%
“…Most of these observations additionally included Charon and some observed Nix and Hydra as well. Other papers by Howett et al (2017) and Grundy et al (2016) describe the color of Charon and a mechanism to explain its red North Pole. The colors of the small satellites have been discussed in Weaver et al (2016).…”
Section: Observationsmentioning
confidence: 99%